2023
DOI: 10.3390/app13095250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamic Stability of Tailing Dams: An Experimental Study on the Dynamic Characteristics of Tailing Silt

Abstract: With the improvement in tailing mining-grade requirements and in mineral processing technology, tailing materials tend to be fine-grained. Under the action of earthquakes, a tailing dam is prone to liquefaction, which endangers the safety and stability of the dam. To further explore the dynamic properties of tailing silt under cyclic stress, through a series of dynamic triaxial experiments, we investigated the growth of the hysteresis curve, the development of pore pressure, and the energy dissipation law of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Rong Gui et al [16] showed that the migration of fine-grained tailings was caused by internal erosion which increased the permeability and reduced the shear strength of the tailings. Fuqi Kang et al [17] showed the dynamic characteristics of tailing silt and investigated the growth of the hysteresis curve, the development of pore pressure, and the energy dissipation law of tailing silt. Xiuwei Chai et al [18] showed that the particle size distribution of tailing sand could affect its strength, and the larger the particle size was, the greater the shear strength would be.…”
Section: Introductionmentioning
confidence: 99%
“…Rong Gui et al [16] showed that the migration of fine-grained tailings was caused by internal erosion which increased the permeability and reduced the shear strength of the tailings. Fuqi Kang et al [17] showed the dynamic characteristics of tailing silt and investigated the growth of the hysteresis curve, the development of pore pressure, and the energy dissipation law of tailing silt. Xiuwei Chai et al [18] showed that the particle size distribution of tailing sand could affect its strength, and the larger the particle size was, the greater the shear strength would be.…”
Section: Introductionmentioning
confidence: 99%